Fluid Dynamic Characteristics of Systolic Blood Flow of the Left Ventricle - Hung, Tin-Kan (2016)
Ejection of blood from the left ventricle to the aorta is studied using two-dimensional Navier–Stokes equations, the work-energy equation and the magnetic resonance imaging of a normal ventricular motion. Vortex shedding in the sinuses of Valsalva is dominated by the aortic jet, flow acceleration and valve motion. Momentums produced by ventricular contraction are in concert with vortices in the ventricle for blood ejection. Shear stresses and net pressures on the aortic valve are calculated during valve opening and closing. The rate of work done by shear and the energy dissipation in the ventricle are small. The Bernoulli energy flux delivered to blood from ventricular contraction is practically balanced by energy flux at the aortic root and the rate change of kinetic energy in the ventricle.